Association of the upregulated expression of focal adhesion kinase with poor prognosis and tumor dissemination in hypopharyngeal cancer. Issue 8 (9th April 2016) - Omura, Go; Ando, Mizuo; Saito, Yuki; Kobayashi, Kenya; Yoshida, Masafumi; Ebihara, Yasuhiro; Kanaya, Kaori; Fujimoto, Chisato; Sakamoto, Takashi; Kondo, Kenji; Asakage, Takahiro; Yamasoba, Tatsuya
Abstract: Background: Focal adhesion kinase (FAK) plays an important role in tumor metastasis. The purpose of this study was to evaluate the significance of FAK expression in surgically treated patients with hypopharyngeal cancer. Methods: We retrospectively reviewed the clinical charts of patients treated at our institution between 2004 and 2012 and identified 87 patients with hypopharyngeal cancer. FAK expression status was retrospectively evaluated using immunohistochemistry. Results: FAK‐positive patients displayed significantly worse disease‐specific survival than FAK‐negative patients ( p  = .001). Multivariate analyses revealed that FAK positivity and extracapsular spread (ECS) were independent, significant adverse prognostic factors. Furthermore, FAK positivity significantly correlated with the number of metastatic lymph nodes ( p  = .048), and FAK‐positive patients displayed a higher incidence of distant metastases ( p  = .009). Conclusion: The current study demonstrated that upregulated FAK expression correlates with poor prognosis and tumor dissemination in surgically treated patients with hypopharyngeal cancer. © 2016 Wiley Periodicals, Inc. Head Neck 38:1164–1169, 2016